Réponses

2013-05-05T12:51:07+02:00

A)  E = (-3x+4) 2 - (2x+5) (-3x+4)

     E = -6x +8  +6x² - 8x  +15x - 20

     E = 6x² + x -12

 

B)  Je ne sais pas dsl 

 

C)   (-3x+4) 2 - (2x+5) (-3x+4) = 0

       (-3x+4) [ 2 - (2x+5) ] = 0

       (-3x+4) (-2x-3) = 0

        -3x+4 = 0 ou -2x-3 = 0

        -3x = -4    ou   -2x = 3

        x = 4/3      ou     x = -3/2

   

 

les solutions de l'équations sont 4/3 et -3/2

 

2013-05-05T13:07:55+02:00

b) il faut un facteur commun

 

(-3x+4)[2-(2x+5)]

(-3x+4)(2-2x-5)

(-3x+4)(-2x-3)